2014
DOI: 10.13057/biodiv/d160101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timber harvest on structural diversity and species composition in hardwood forests

Abstract: Tavankar F, Bonyad AE. 2015. Effects of timber harvest on structural diversity and species composition in hardwood forests. Biodiversitas 16: 1-9. Forest management leads to changes in structure and species composition of stands. In this research vertical and horizontal structure and species composition were compared in two harvested and protected stands in the Caspian forest of Iran. The results indicated the tree and seedling density, total basal area and stand volume was significantly (P < 0.01) higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
12
1
1
Order By: Relevance
“…Some studies have shown a decline in stem density in forests with the removal of fuelwood and fodder from live-standing trees (Jiang et al 2015;Tavankar & Bonyad 2015), but there was little evidence of this occurring in our study area. Stem density is generally associated with the intensity of silviculture practices such as thinning (Thomas et al 1999), which is adopted by almost every CF in Charnawati to extract fuelwood and timber.…”
Section: Relationships Between Plant Diversity Attributes and Forest contrasting
confidence: 65%
“…Some studies have shown a decline in stem density in forests with the removal of fuelwood and fodder from live-standing trees (Jiang et al 2015;Tavankar & Bonyad 2015), but there was little evidence of this occurring in our study area. Stem density is generally associated with the intensity of silviculture practices such as thinning (Thomas et al 1999), which is adopted by almost every CF in Charnawati to extract fuelwood and timber.…”
Section: Relationships Between Plant Diversity Attributes and Forest contrasting
confidence: 65%
“…However, Onaindia, Dominguez, Albizu, Garbisu, and Amezaga () showed that in northern Spain, U. glabra was the third most abundant tree in old‐growth forest (16% cover compared to 53% in dominant Quercus robur and 24% in Fagus sylvatica ), yet it was absent from clear‐cut areas felled 30 and 60 years ago. Similarly, Tavankar and Bonyad () found stem density of U. glabra was higher in protected forest (10.8 stems/ha) than in harvested stands (3.3 stems/ha; time since harvesting was unstated) in Iran. This suggests that U. glabra is sensitive to clear‐felling in open, warm areas, possibly due to the removal of shady, humid conditions created by surrounding trees.…”
Section: Response To Biotic Factorsmentioning
confidence: 85%
“…Forest protection should aim at ensuring that forests continue to perform all their productive, socio-economic and environmental functions in the future. It is widely accepted, that a structurally diverse stand provides living space for a larger number of organisms (Tavankar and Bonyad 2015). Iran is a country with low forest cover (UNFF 2005), so that only 7.3% of it is covered by forest areas (FAO 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Species importance value (SIV) for each tree specious was calculated by: SIV= Relative density (RD) + relative frequency (RF) + relative dominance (RD). Basal area was considered for dominancy and relative dominance (RD) calculated by: RD = (basal area of a species × 100) / total basal area of all species (Amoroso et al 2011;Pourbabaei et al 2013;Tavankar and Bonyad, 2015). Confidence intervals on the means calculated as accuracy by: CI% = ( , where CI is confidence interval, is standard error, t 95% is t value in 95% confidence level from t table and is mean (Zobeiri 2007).…”
Section: Data Collection and Analysismentioning
confidence: 99%